Nasal high-frequency jet ventilation (NHFJV) as a novel means of respiratory support in extremely low birth weight infants - Keel, Jessica (J Perinatol, 2021)
OBJECTIVE: Describe our experience of successfully using nasal high-frequency jet ventilation (NHFJV) in extremely low birth weight infants with respiratory failure. STUDY DESIGN: A retrospective review was conducted on 16 infants with birth weights <1000 g who received NHFJV from 2015 to 2019. Successful use was defined as avoiding intubation for at least 72 hours and demonstrating tolerance after being placed on NHFJV. RESULTS: Median gestational age was 24.5 weeks (IQR 24, 25), and weight at the start of NHFJV 1090 g (IQR 905, 1250). NHFJV was used successfully in 13/16 (81%) infants with a median duration of 7 days (IQR 3, 12). Days on invasive (30 vs. 186) and noninvasive (46 vs. 81) ventilation were shorter when compared to those who failed the use of NHFJV. CONCLUSION: This is the first reported case series for the successful use of NHFJV. Our study highlights the feasibility of a potential new mode of noninvasive respiratory support.